A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, K.S. (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.
MA. International Affairs
Keywords: Economic Community of Central African States (ECCAS); Abuja Treaty; ECOWAS